Effectiveness & mechanism of phytoconstituents against Candida biofilm - Madhulika Jha; Jahanvi Agarwal; Pankaj Gautam; Navin Kumar (Environment Conservation Journal)
Fungal biofilms are complex and resistant structures that pose a challenge in treating infections. Active phytoconstituents are natural compounds derived from plants that have shown promising antifungal properties. Many reports of antimicrobial resistance in human pathogenic fungi demand immediate attention to explore new therapeutics. Plant-based therapeutics alone or in conjugated form have shown promising results against fungal biofilms. Several studies have reported the effectiveness of various phyto constituents in inhibiting the formation and dispersal of fungal biofilm. Different mechanisms, such as disrupting cell signaling pathways, inhibiting biofilm matrix formation, and altering the fungal cell wall structure, have demonstrated the effectiveness of these compounds. This review focuses on the use of active phytoconstituents as potential agents against fungal biofilm.